Mental Well-Being and Its Relationship to Learning Engagement and Academic Achievement of Secondary School Students in Sri Lanka - Olokku Patabendige Dileepa Thathsara; Veena Shenoy (Journal of Education Psychology and Social Development, 2026)
Mental well-being is widely recognized as an important factor influencing learning engagement and academic achievement, particularly among secondary school students who experience increasing academic, emotional, and social pressures. However, empirical evidence from the Sri Lankan secondary school context remains limited. This study investigated the relationship between mental well-being, learning engagement, and academic achievement among secondary school students in Sri Lanka. A convergent parallel mixed-methods design was employed to obtain a comprehensive understanding of the research problem. The sample consisted of 60 students from Grades 9 and 10 selected through simple random sampling from a single secondary school. Quantitative data were collected using a structured questionnaire based on established psychological well-being frameworks. Mental well-being was measured using a standardized scale with acceptable reliability (Cronbach’s alpha = 0.84). Learning engagement was operationalized through indicators of attention, motivation, and classroom participation, while academic achievement was measured using students’ term test scores. In addition, qualitative data were collected through semi-structured interviews with 12 purposive selected students and classroom observations, and analyzed using thematic analysis. Quantitative data were analyzed using descriptive statistics and Pearson correlation analysis. The findings indicated a moderate positive relationship between mental well-being and academic achievement (r = 0.52, p < 0.01), as well as between mental well-being and learning engagement (r = 0.57, p < 0.01). Qualitative findings supported these results, indicating that students with higher mental well-being demonstrated greater concentration, intrinsic motivation, and active classroom participation, while students experiencing higher stress showed reduced engagement. In conclusion, the study highlights that mental well-being is significantly associated with both learning engagement and academic achievement, emphasizing the need for school-based interventions to support students’ psychological well-being.